2021
DOI: 10.1002/phar.2609
|View full text |Cite
|
Sign up to set email alerts
|

The association between urate‐lowering therapies and treatment‐related adverse events, liver damage, and major adverse cardiovascular events (MACE): A network meta‐analysis of randomized trials

Abstract: Purpose Hyperuricemia is a common disease that may lead to gout, renal damage, and cardiovascular events. Oral medication is the main treatment for hyperuricemia patients when lifestyle intervention fails. An evaluation of the safety of various urate‐lowering therapies (ULTs) is integral to clinical decision‐making. We constructed a network meta‐analysis (NMA) to evaluate the safety of oral ULTs. Methods MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials were searched up to April 1, 2021, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
(302 reference statements)
0
7
0
Order By: Relevance
“…In clinical practice, the first-line drugs typically used for hyperuricemia are associated with severe liver and kidney damage, thereby limiting their safe application. 6 Fortunately, RA is a natural medicinal and edible Chinese medicine with a long history of application in the treatment of metabolic disorders. 21 , 22 More importantly, contemporary pharmacological investigations have indicated that RA can be used to lower UA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, the first-line drugs typically used for hyperuricemia are associated with severe liver and kidney damage, thereby limiting their safe application. 6 Fortunately, RA is a natural medicinal and edible Chinese medicine with a long history of application in the treatment of metabolic disorders. 21 , 22 More importantly, contemporary pharmacological investigations have indicated that RA can be used to lower UA.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Obviously, there are several only UA-lowering medicines in the clinic, such as allopurinol (ALL) and benzbromarone. 5 Unfortunately, these chemical drugs are not suitable for a long-term and effective therapeutic schedule due to the reported side effects, 6 especially hepatorenal toxicity. Hence, it is necessary to seek a safer and more valid strategy to treat hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%
“…MACEs were defined using International Classification of Diseases, Clinical Modification, Tenth Revision (ICD-10-CM) diagnosis codes, including cardiovascular death, non-fatal myocardial infarction, and non-fatal stroke ( Bosco et al, 2021 ; Zhang et al, 2021 ), including acute myocardial infarction (AMI)-induced left heart failure (LHF), ventricular fibrillation (VF)-induced sudden death, and cordial arrhythmia induced by valvular diseases, myocardiopathy, and myocarditis. Thus, MACEs can be detailed as all of the preferred terms containing the keywords “card,” “heart,” “ventricular,” “cereb,” “brain” coupled with “infarction,” “stroke,” “death,” “itis,” “pathy,” “failure,” and “fibri,” which were determined by the Standardized MedDRA Query (version 23.0) terminology ( Katsuhara and Ikeda, 2021 ) ( Supplementary Table S1 , MACEs).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding medication, a detailed overview of specific drugs for the management of elevated serum uric acid is beyond the scope of this review. Briefly, although uric acid lowering drugs can beneficially affect surrogate CVD markers, a recent meta-analysis showed that there were no statistically significant differences in CVD risk between three uric acid lowering medications (allopurinol, febuxostat and lesinurad combined with xanthine oxidase inhibitor) and placebo [21 ▪▪ ]. It is also worth mentioning that there are several drugs (e.g.…”
Section: Uric Acid and Cardiovascular Riskmentioning
confidence: 99%